Improved characteristics of radio frequency interdigital capacitor - Lim, Yun Rou (2006)
Technology advances in complimentary-metal-oxide-silicon (CMOS) process offer some interesting possibilities for radio frequency (RF) circuit designers. Some circuits that would have to be done with GaAs monolithic microwave integrated circuits (MMICs), for instance, are now possible in CMOS. While the transistor speed has been improving significantly, fuller integration of RF integrated circuits (RFICs) is often retarded by the absence of high quality, high rangebility and efficient on-chip passive components. This thesis presents the possibilities of improving the characteristics of an RF capacitor having interdigital configuration. Modifications in the form of combline structure were introduced into the conventional configuration to improve the capacitor characteristics. Performance in the form of capacitance and Quality, Q, factor were investigated through simulations using electromagnetic simulation software, Ansoft HFSS. The analysis and comparison between conventional and the proposed interdigital capacitor (IDC) with combline structure were discussed in detail. It can be concluded that the proposed IDC with combline structure improves the capacitance of an IDC. The optimum combline configuration which achieved useful capacitance with sufficiently high Q factor is the design with 110 mils effective finger length. It produces 5.48 pF capacitance at first resonance of 2 GHz, with sufficiently high Q factor of 13.88. This is a factor of 1.72 higher than the corresponding conventional IDC having 3.18 pF at first resonance of 3 GHz albeit 10 % slightly higher Q factor of 15.41.